(untitled) (Damascus University Journal of agriculture sciences, 2024)
A study conducted to compare several treatments for controlling root-knot nematodes on the Cucumber plant var Prince, The research was carried out in pots in a greenhouse in Tartous city during the year 2022, the treatments included (fluopyaram, imicyafos, azedracht leaf powder, neem cake, azedracht leaf powder + imicyafos ) in terms of growth and root wet and dry weight and complexity coefficient, in addition to numerical density of infective the second larval stage juvenile (J2). The results showed the superiority of Fluopyaram treatment in controlling all stages of nematodes present in the soil, and the complexity coefficient was 0, followed by the treatment of azedarcht leaves powder + Imicyafos30% with a density of 12.33 individuals, and the complexity factor of 0.666 was recorded. The pesticide Imicyafos increased the average growth of cucumber plant, where the lengths of 185 and 167.33 cm were recorded, respectively, while the control was 103 cm, and the powdered neem cake was 142.33 cm, while the weights of wet roots ranged from 39 g and 22 g, the largest of which was for Fluopyaram treatment and the lowest for the control treatment, and the dry root weight ranged from 23g and 12g.